A política de crescimento econômico do Governo Lula: o Programa de Aceleração do Crescimento - PAC - Deporte, Henrique Fernando Suini (2011)
Dados da TDE em outro idioma Idioma Ingles Título Palavras-chave Lula government; Public policy; Development growth; Economic growth; Growth Acceleration Program; Resumo This paper analyzes the political-economic growth of the Lula government, emphasizing the Growth Acceleration Program (PAC). The first chapter discusses the model and the government's economic policy, year after year, presenting the main macroeconomic indicators. The second chapter presents the Growth Acceleration Program since its inception, its planning in three areas logistics, energy and social and urban with regional decentralization, institutional arrangements and budget and finances implementation. The third chapter makes a comparison of the Growth Acceleration Program, Plan Goals (JK government) and the II PND (Geisel government), because they are the most studied economic development plans of specific literature in order to verify the similarities and differences. The results show the high performance of the PAC, both in terms of works as the point of view of institutional measures and may become the country's history, not as an economic program that changed the Brazilian productive structure, just like the Plan Goals and II PND, as a program that has worked more effectively the issue of sanitation and housing shortage